Por detrás de uma coleção do Museu Nacional do Rio de Janeiro: vozes, silêncios e desafios - Cecilia de Oliveira Ewbank; Manuel Ferreira Lima Filho (Midas: Museus e Estudos Interdisciplinares)
The present paper aims to contribute to the reflection on the current silencing of the biographical characteristics of ethnographic collections exhibited in museums, especially with regard to the context of their acquisition, through the analysis of the inventory of a Karajá collection at the National Museum (NM) of Rio de Janeiro. This is the collection collected by the north-American anthropologist William Lipkind (1904-1974) when he came to Brazil to carry out field research in the Araguaia region of Goiás, between 1938 and 1939, and which was incorporated into the NM as part of the national policy of inspection of scientific expeditions in the country. The questioning about the recording of the W. Lipkind ethnographic collection in NM allowed us to infer about different times of acquisition and incorporation, highlighting the challenges of understanding the collection through the relation between subject and object. More than in collection inventories, the analysis of the configuration of the collection took place in archival documents that safeguard the memory of the identity bonds maintained by the objects with the characters that outline their narrative.